Social Entrepreneurial Intention: A Pls-Sem Approach - Aisyah Bahiah Aidul Bahrein, Mohd Nazri Zakaria, Noorshella Che Nawi, Azwan Abdullah (International Journal of Advanced Science and Technology, 2020)
The aim of this paper is to examine the effects of perceived desirability and perceived feasibility on social entrepreneurial intention and the moderating role of culture. The study on culture as a moderator is still limited and this study can provide a better explanation regarding the moderating impact of culture. The data collected from 386 undergraduate and postgraduate students are analysed by using partial least squares structural equation modelling (PLS-SEM). The findings discover that perceived feasibility has a positively significant relation with social entrepreneurial intention while perceived feasibility does not and culture is proven to not moderate the existing relationships in this study. Lastly, some limitations and several recommendations for future studies are discussed. Keywords: Culture, perceived desirability, perceived feasibility and social entrepreneurial intention